(3eSGdc GdCagGe aj BjGJ GdCMcGes - (3GdLhGO GdHZOGOj , LhGO Hf SYO (B((3Ch SYjO(B) (3Hf LhGO GdHZOGOj GdcGXej, GdLhGO GdHZOGOj,J (B1065 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd deG cGf ef CLd GdfYe hChbQ GdbSe GSJaGOI GdCMcGe GdTQYjI ef GdBjGJ GdbQBfjI s
(3BNQgG (B:s
(3UhJ Ydi GdeTghQ hEf NGda ajg LeGYI fYe GdENdGU ai GdfjI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B142 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B165s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B472s
Keywords: (3abg GdePGgH GdCNQis